Understanding Youths: A Training Program for Leaders of University Health Programs - Mutchinick, Agustina; Jalley, María V.; Cacchiarelli San Román, Nicolás; Delorenzi, Érica; Berk, Michelle; Kobelt, María V.; Alonso, Valeria; Piola, Constanza; Carrió, Silvia; Soza, Tania; Pinto, Julieta; Ferrari, Martina; et al. (Revista del Hospital Italiano de Buenos Aires, 2024)
Introduction: The article presents and analyzes a teacher training strategy implemented in a privateuniversity in the city of Buenos Aires, Argentina. This initiative responds to a challenging scenario currently faced by educators and educational program leaders: undergraduate students show limited participation in the activities offered by the university, and residents are demanding better training and working conditions, including fewer hours in the hospital, better treatment from supervisors, or show less willingness to take on additional responsibilities. Additionally, there is a growing number of support consultations regarding difficulties with concentration, fatigue, discouragement, self-imposed pressure, and a lack of confidence in their abilities. These situations prompt us, as educators, to reflect on and examine the world of today’s youth to better align our interventions with their motivations and expectations.Development: In this context, we held a series of sessions aimed at sharing questions, fostering debates, and considering possible actions to address the current demands of those in training at our institution.Results: In this article, we will share the designed program and the results of its implementation. Theapproach began with an individual perspective and gradually progressed toward collaborative, wellgrounded constructs rooted in our institution.Conclusions: This work was a first step in identifying and understanding the decisions and expectationsof young people to support them in their educational journeys in a meaningful, relevant way that alignswith the current socio-historical context.
Keywords: Youths; Higher Education; Iniciative; Health Sciences